The DNA Methylation Status of Wnt and Tgfβ Signals Is a Key Factor on Functional Regulation of Skeletal Muscle Satellite Cell Development - Zhang, Weiya; Zhang, Saixian; Xu, Yueyuan; Ma, Yunlong; Zhang, Dingxiao; Li, Xinyun; Zhao, Shuhong (Frontiers in Genetics, 2019)
DNA methylation is an important form of epigenetic regulation that can regulate the expression of genes and the development of tissues. Muscle satellite cells play an important role in skeletal muscle development and regeneration. Therefore, the DNA methylation status of genes in satellite cells is important in the regulation of the development of skeletal muscle. This study systematically investigated the changes of genome-wide DNA methylation in satellite cells during skeletal muscle development. According to the MeDIP-Seq data, 52,809-123,317 peaks were obtained for each sample, covering 0.70%-1.79% of the genome. The number of reads and peaks was highest in the intron regions followed by the CDS regions. A total of 96,609 DMRs were identified between any two time points. Among them 6198 DMRs were annotated into the gene promoter regions, corresponding to 4726 DMGs. By combining the MeDIP-Seq and RNA-Seq data, a total of 202 overlap genes were obtained between DMGs and DEGs. GO and Pathway analysis revealed that the overlap genes were mainly involved in 128 biological processes and 23 pathways. Among the biological processes, terms related to regulation of cell proliferation and Wnt signaling pathway were significantly different. Gene-gene interaction analysis showed that Wnt5a, Wnt9a, and Tgfβ1 were the key nodes in the network. Furthermore, the expression level of Wnt5a, Wnt9a, and Tgfβ1 genes could be influenced by the methylation status of promoter region during skeletal muscle development. These results indicated that the Wnt and Tgfβ signaling pathways may play an important role in functional regulation of satellite cells, and the DNA methylation status of Wnt and Tgfβ signals is a key regulatory factor during skeletal muscle development. This study provided new insights into the effects of genome-wide methylation on the function of satellite cells.